Standardized Certification for Indonesian Female Migrant Workers: Towards Qualified Domestic Workers - Kiki Zakiah; Chairiawaty (Salasika, 2018)
This research paper is entitled Standardized Certification for Indonesian Female Migrant Workers: Towards Qualified Domestic Workers. The problem of the research was derived from the fact that Indonesia is the highest sender of female migrant workers. Based on the data taken from BNP2TKI, female migrant workers from Indonesia mostly work in domestic sector as housemaids. Unfortunately, most of them are still considered unskilled. There is a quite significant difference between Philippines and Indonesia’s government policy in positioning migrant workers. The government of Philippines is very serious about preparing policy to position migrant workers by providing diplomatic protection, since they realize that the income from remittance can reach 20 %, and preparing public education policy concerning migration in the form of massive pre-departure orientation in migrant worker areas. In order for Indonesian migrant workers to compete with other workers, government is required to prepare the migrant workers to fulfill requirements and standards and prepare the agenda for strengthening legal recognition of their work as housemaids. Nusron Wahid, BNP2TKI chairperson, stated that Indonesian migrant workers need to improve their skills. This is necessarily required to change the face of Indonesian migrant workers. Skill improvement program for migrant workers is provided by Labor Training Centers that can be found in every province in Indonesia. Labor Training Center offers some programs and activities both for migrant workers and public, so they can improve their knowledge, skill and character This research focused on how migrant workers empower themselves in terms of knowledge, skill, and character building through certified programs given by Labor Training Center. The research problems can be identified as follows: (1) to what extent can the certified programs given by Labor Training Center upgrade migrant worker’s knowledge, (2) to what extent can the certified programs given by Labor Training Center increase migrant worker’s skill, and (3) to what extent can the certified programs given by Labor Training Center improve migran workers’ character. The objectives of the research are: (1) to find out the map of the knowledge development of migrant workers taking the certified programs in Labor Training Center; (2) to know the improvement of migrant workers’ skill s, and (3) to find out the improvement of migrant workers’ character s . The research used descriptive qualitative method. The data were gathered from previous research, in form of journals, documents and participant observation. From the data gathered, it was found out that the initiation programs organized by Labor Training Center was the dissemination of information about working abroad. This was aimed to give information to those who wanted to work outside Indonesia legally, securely, and appropriately, and to give information on opportunities to find some jobs overseas along with the advantages and disadvantages. This is one way to prepare Indonesian migrant workers to be ready to work outsideIndonesia. This means that migrant workers are given some knowledge to be well-prepared workers. In order to increase the skill of migrant workers, Labor Training Center offered some skill upgrading programs supported by practices. The skills are divided into: personal skill, social skill, and technology skill such as housework activities, social interaction, communication media, and many more. The aim was to improve the skill of migrant workers. As for character development, Labor Training Center offered some trainings, such as motivation, ethics, self-defense, work ethos, and personality. These are very needed to ensure migrant workers’ mental preparedness. The findings of the research showed that the knowledge of the migrant workers increased after they took part in the programs conducted by Labor Training Center. They knew that they needed to have legal contract when they worked overseas so that they could work safely, securely and appropriately. They would not be kicked out form a certain country any more. In terms of skill, the migrant worker could increase their social and technology skill to equip them to work overseas, whereas in terms of character building, the migrant workers could have positive mind and strong confidence to work overseas.